Effects of Propofol Versus Sevoflurane on Postoperative Breast Cancer Prognosis: A Narrative Review - Fang, Panpan; Zhou, Jiaqi; Xia, Zhengyuan; Lu, Yao; Liu, Xuesheng (Frontiers in Oncology, 2022)
Perioperative interventions produce substantial biologic perturbations which are associated with the risk of recurrence after cancer surgery. The changes of tumor microenvironment caused by anesthetic drugs received increasing attention. Till now, it’s still unclear whether or not anesthetic drugs may exert positive or negative impact on cancer outcomes after surgery. Breast cancer is the most common tumor and the leading cause of cancer deaths in women. Propofol and sevoflurane are respectively the most commonly used intravenous and inhaled anesthetics. Debates regarding which of the two most commonly used anesthetics may relatively contribute to the recurrence and metastasis vulnerability of breast cancer postoperatively remain. This review aimed to provide a comprehensive view about the effect of propofol versus sevoflurane on the prognosis of breast cancer obtained from pre-clinical studies and clinical studies. Laboratory and animal studies have demonstrated that sevoflurane may enhance the recurrence and metastasis of breast cancer, while propofol is more likely to reduce the activity of breast cancer cells by attenuating the suppression of the immune system, promoting tumor cells apoptosis, and through other direct anti-tumor effects. However, retrospective clinical studies have shown contradictory results about the effects of propofol and sevoflurane on long-term survival in breast cancer patients. Furthermore, recent prospective studies did not identify significant differences between propofol and sevoflurane in breast cancer metastasis and recurrence. Therefore, more preclinical studies and randomized controlled studies are needed to guide anesthetics choice for breast cancer patients.